Pelatihan Aplikasi E-Learning “MojadiPro” Berbasis Android untuk Siswa SMK IT Raflesia Depok - Agus Subekti; Zico Pratama Putra; Dwiza Riana; Hilman Ferdinandus Pardede (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
SMK IT Raflesia Depok is one of the high schools in the Depok City area which currently has a website that is used as a medium of information and communication, but does not yet provide teaching material services online. Apart from getting subject matter from school, students are usually still looking for additional material by attending private classes. With the development of technology that has developed in the field of education, access to subject matter can be done online, or what is commonly called e-learning. In order to carry out the Tri Dharma of Higher Education, Nusa Mandiri University held an android-based